2018
DOI: 10.1038/s41598-018-19261-w
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress via inhibition of the mitochondrial electron transport and Nrf-2-mediated anti-oxidative response regulate the cytotoxic activity of plumbagin

Abstract: Plumbagin, an anti-cancer agent, is toxic to cells of multiple species. We investigated if plumbagin targets conserved biochemical processes. Plumbagin induced DNA damage and apoptosis in cells of diverse mutational background with comparable potency. A 3–5 fold increase in intracellular oxygen radicals occurred in response to plumbagin. Neutralization of the reactive oxygen species by N-acetylcysteine blocked apoptosis, indicating a central role for oxidative stress in plumbagin-mediated cell death. Plumbagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 51 publications
0
43
0
Order By: Relevance
“…Our experiments with human cancer cell lines showed that plumbagin induces oxidative stress [20]. When the CTAC cells were labeled with the ROS sensing fluorescent dye, H2DCFDA and treated with plumbagin (5 µM), a rapid increase in intracellular oxygen radicals was detected by flow cytometry analysis of the cells ( Fig.…”
Section: Plumbagin Causes Oxidative Stress In Canine Cancer Cellsmentioning
confidence: 78%
See 4 more Smart Citations
“…Our experiments with human cancer cell lines showed that plumbagin induces oxidative stress [20]. When the CTAC cells were labeled with the ROS sensing fluorescent dye, H2DCFDA and treated with plumbagin (5 µM), a rapid increase in intracellular oxygen radicals was detected by flow cytometry analysis of the cells ( Fig.…”
Section: Plumbagin Causes Oxidative Stress In Canine Cancer Cellsmentioning
confidence: 78%
“…We recently demonstrated that plumbagin decreased the intracellular ATP levels in cancer cells [20]. We therefore tested if the inhibition of NKA observed in plumbagin-treated CTAC was due to decreased availability of intracellular ATP.…”
Section: Inhibition Of Nka By Plumbagin Is Not Due To Decrease In Intmentioning
confidence: 98%
See 3 more Smart Citations